Implementasi Algoritma Rivest Shamir Adleman atas Ring Dedekind - Ladunniyyah, Zakiyya Dzul; Khudzaifah, Muhammad; Herawati, Erna (Jurnal Riset Mahasiswa Matematika, 2024)
The issue of security and confidentiality of data or messages is very important so efforts are needed to maintain the security and confidentiality of messages, one of which is with cryptography. This study aims to determine the implementation of the RSA algorithm over the Dedekind ring to secure text messages. This implementation is done by modifying the key formation, encryption, and decryption processes of the RSA cryptographic algorithm to match the Dedekind ring used. The research stage carried out is to form a key on the RSA algorithm over the Dedekind ring, then construct an encryption and decryption algorithm to secure messages with RSA over the Dedekind ring. From this research, results were obtained in the form of an RSA message encoding algorithm in accordance with the Dedekind ring where the Dedekind ring was used in the key formation process. Furthermore, the encryption and decryption process is carried out with the RSA algorithm. The conclusion of this study is that the implementation of the RSA algorithm over the Dedekind ring can produce a wider public key where the public key used is any member number of the set of maximal ideal products on the Dedekind ring.